Roadmap for Renewal: A Shared Platform in the Food Industry - Annu Kotiranta; Timo Seppälä; Antti-Jussi Tahvanainen; Markus Hemminki; Juri Mattila; Samuli Sadeoja; Tea Tähtinen (The Research Institute of the Finnish Economy (ETLA), 2017)
The majority of digital platform research has focused on consumer-centric platforms. Driven by the vast growth potential of direct consumer market access, industrial communities locked behind the conventional gatekeepers in their respective value chains have lately started to tinker with their own platform creation initiatives. Aided by fifteen food industry actors, we identify two critical managerial prerequisites for and design a six-step roadmap towards a participatory infrastructure platform – a platform that allows platform participants to share proprietary data and – by exploiting the data – to create new artifacts in consumer-centric marketplaces. Beyond product innovations, sharing data also enables new optimization layers for operational efficiencies and increased productivity on the industry level. In exploring the participants' commitment and willingness to shift towards such a platform model, we found three operational data types that the companies would readily be willing to share: 1) transportation data, 2) warehousing data, and 3) demand/supply data managed with decentralized governance models. In the short term, each data type could provide the foundation for the establishment of a specific type of an operational platform: a transportation platform, a warehousing platform, or a market platform. The latter would provide the long-sought direct access to consumer markets. Building on these models, we identify another three strategic avenues for long-term joint development: 1) algorithmic development and evolution of the platform, 2) cross-industry interoperability of the platform, and 3) interoperability with competing platforms. Laying out a roadmap of evolving platform models towards a consumer-driven business ecosystem, we contribute to the empirical literature on industrial platform creation.
Keywords: L6; L66; L8; L81; L86; 330; Platform; E-commerce; Multi-sided markets; Food industry; Internetportal; Online-Handel; Netzwerkökonomik; Ernährungsindustrie; Finnland